The Casual Relationship of Financial Management: A Study among Northeasterners of Thailand - Samsuwan, Lanliya; Socatiyanurak, Montree (Hatyai Academic Journal, 2021)
This study was aimed at (1) examining the causal relationship in financial literacy, risk in financial planning, financial planning motivation, self-efficacy, and retirement financial planning among people living in the northeastern region of Thailand, and at (2) proposing policy recommendations on financial literacy, risk in financial planning, financial planning motivation, self-efficacy, and retirement financial planning of the targeted group. Mixed methods research was adopted for the study. For the quantitative research approach, 460 respondents living in five provinces in the northeastern region were the samples of this study. Those five provinces included Buriram, Loei, Nakhon Phanom, Udon Thani, and Surin. Proportional sampling was used to divide the working population base aged between 25 and 59 years old. Then, accidental sampling was applied. A total number of 460 samples inhabiting the five Northeastern provinces was proportionally randomized relying on a quota-based accidental sampling technique. A focus group of nine experts was conducted to review the draft of policy recommendations. The result found that financial literacy had a positive direct effect on self-efficacy and retirement financial planning. Risk in financial planning was found to have a positive direct effect on self-efficacy. Also, it was found that financial planning motivation had a positive direct effect on self-efficacy and retirement financial planning. Besides, the structural equation modeling also indicated that self-efficacy had a positive direct effect on retirement financial planning. According to the focus group, it was obvious that self-efficacy was the most influential factor for retirement planning, followed by financial planning motivation, financial literacy, and risk in financial planning, respectively.